The effect of education and telephone follow-up after discharge (telenursing) on care pressure and resilience in caregivers of bipolar patients: A quasi-experimental study - Peiman Fereidouni Sarijeh; Ali Khatib; Soheileddin Salmani; Maryam Fransiz (Journal of Research Development in Nursing and Midwifery)
Background: Family caregivers face a caregiving burden due to providing care to patients with mental illness. It is essential to employ appropriate strategies to reduce the caregiving burden and increase resilience. Telenursing, as an accessible and cost-effective strategy, enables continued support and education after discharge. This study was conducted with aim to evaluate the effect of education and telephone follow-up (telenursing) on care burden and resilience in caregivers of patients with bipolar disorder. Methods: This quasi-experimental study was conducted from September 2024 to March 2025 at Razi Psychiatric Hospital, Tehran, Iran. A total of 60 caregivers of bipolar disorder patients were selected through convenience sampling. Participants were then randomly assigned to the intervention (n=30) and control (n=30) groups using a simple randomization method. The intervention group received eight group-based telenursing sessions (two sessions per week, 40–50 minutes each). The control group received only routine discharge education. Data were collected using the Caregiver Burden Scale and the Connor-Davidson Resilience Scale before and after the intervention. The data were analyzed using SPSS software (version 25) and independent and paired t-tests. P<0.05 was considered significant. Results: After the intervention, the mean caregiving burden in the intervention group significantly decreased (28.03±16.72) compared to the control group (58.93 ± 12.18) (p<0.0001). Also, the mean resilience in the intervention group significantly increased (36.63 ± 1.86) compared to the control group (26.10±8.26) (p<0.0001). These results indicate the strong evidence for effectiveness of education and telenursing in reducing caregiving burden (p<0.0001) and increasing resilience of caregivers of bipolar patients (p<0.0001). Conclusion: The results indicate that telenursing has a positive effect on reducing caregiving pressure and increasing the resilience in caregivers of patients with bipolar disorder. This type of support is useful for providing comprehensive care and maintaining the health of family caregivers.